Coding Creativity: Insights from Matt Deslauriers on Generative Art. - ÖZKERIM, MERVE GÜVEN (Hyperrhiz, 2025)
This interview with Matt Deslauriers delves into his creative process, inspirations, and perspectives on algorithmic art, blockchain technology, and the evolving dynamics of originality, creativity, and power in the post-digital art world.